EFFECT OF USING FENUGREEK SEEDS ON SOME PHYSICAL AND BIOCHEMICAL CHARACTERS OF BLOOD IN AWASSI RAMS - Mohammad Al-Moteoty (Mesopotamia Journal of Agriculture)
This study was conducted in the field of animal resources department-university of mosul on 15 Awassi males (2-3 years) were randomly divided into three equal group and these groups were fed on three rations contain same crude protein and metabolizable energy but different in Fenugreek seeds percentage(0,5, 10 %) for seventy five days(15/11/2012 - 1/2/2013). Results showed that feeding of Fenugreek seeds was increased significantly (P ≤ 0.05) on Hemoglobin concentration (Hb), Red Blood Cells (RBC), globulin, urea concentration, calcium in blood serum and decreased significantly (P ≤ 0.05) on Erythrocyte Sedimentation seeds on, urine (Ph), total protein, albumin, albumin / globulin, Potassium, in Rate (ESR), Whit Blood Cells (WBC), cholesterol, triglyceride and sodium in blood serum and There were no significantly effects (P ≤ 0.05)of the Fenugreek blood serum,Packed Cell Volum (PCV),), Mean Corpuscular Hemoglobin (M.C.H),Mean Corpuscular volume (M.C.V).,Mean Corpuscular Hemoglobin Concentration (M.C.H.C), glucose sugar, were recorded as compared with the control group rams.